Hak Tenurial Masyarakat Adat Dalam Pengelolaan Hutan - Haryanto, Ririn V.; Tjoa, Marthina; Marasabessy, Husain (Universitas Pattimura, 2019)
The certainty of tenure rights has been a problem related to the use of forests by indigenous peoples. This study aims to identify indigenous peoples' existence and find out the forms of customary tenure rights in forest land management. The method used in this study is a qualitative method with a descriptive analysis to provide a true and accurate picture of the tenure rights of indigenous peoples. Research results show that indigenous peoples are still healthy with traditional institutions, and universal values ​​are always maintained. The tenure system in Wakal is controlled by the State, control by the clan, and control by the individual family. There are forms of tenure rights in the three tenure systems that include ownership rights, tenure rights, exclusive voting rights, and proprietary use rights that are still actively applied in forest management.